Development of a Platform for Massivel Parallel Single-Cell Genomic and Expression Analysis. - Cavanagh, Peter. (Tufts University. Tisch Library., 2018)
Submitted in partial fulfillment of the grant requirement of the Tufts Summer Scholars Program.